2009
DOI: 10.4039/n09-004
|View full text |Cite
|
Sign up to set email alerts
|

Assemblage of Hymenoptera arriving at logs colonized byIps pini(Coleoptera: Curculionidae: Scolytinae) and its microbial symbionts in western Montana

Abstract: Colonization of a tree by bark beetles and their symbionts creates a new habitat for a diverse assemblage of arthropods, including competing herbivores, xylophages, fungivores, saprophages, predators, and parasitoids. Understanding these assemblages is important for evaluating nontarget effects of various management tactics and for subsequently evaluating how changes in climate, the presence of invasive species, and altered forestry practices and land-use tenure may affect biodiversity. We characterized the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…However, Vega et al (1999) reported that C. stephanoderis was the most abundant coffee berry borer parasitoid in Cote d'Ivoire, followed by Phymasticus coffeae (Eulophidae). Moreover, Boone et al (2009) reported that from a survey of hymenopterans attracted to logs colonized by Ips pini Woods & Bright (Coleoptera: Curculionidae: Scolytinae) in western Montana, pteromalids were the most important group related to Scolytinae, but less than 1% of the trapped specimens were associated with Scolytinae. These lists and examples are of dubious worth because they are primarily parasites of the less-hidden bark beetles.…”
Section: Discussionmentioning
confidence: 99%
“…However, Vega et al (1999) reported that C. stephanoderis was the most abundant coffee berry borer parasitoid in Cote d'Ivoire, followed by Phymasticus coffeae (Eulophidae). Moreover, Boone et al (2009) reported that from a survey of hymenopterans attracted to logs colonized by Ips pini Woods & Bright (Coleoptera: Curculionidae: Scolytinae) in western Montana, pteromalids were the most important group related to Scolytinae, but less than 1% of the trapped specimens were associated with Scolytinae. These lists and examples are of dubious worth because they are primarily parasites of the less-hidden bark beetles.…”
Section: Discussionmentioning
confidence: 99%
“…The pine engravers, Ips pini (Say) (Coleoptera: Scolytinae), are endemic, transcontinentally distributed bark beetles of North America (Boone et al 2009) that parasitize weakened or recently dead pine (Pinus) and spruce (Picea) trees (Wood 1982).…”
Section: Acoustic Signals In Ips Pinimentioning
confidence: 99%
“…Nevertheless, the broad frequency bandwidth in Ips pini signals allow them to be perceived by a variety of predators and parasitoids, which, in nature, includes clerid beetles (i.e. Thanasimus dubius, and Enoclerus lecontei) (Coleoptera: Cleridae), clown beetles (Histeridae), darkling beetles (Tenebrionidae), bark-gnawing beetles (trogossitidae), robber flies (Diptera: Asilidae), and the parasitic wasp, Tomicobia tibialis, (Hymenoptera: Pteromalidae) (Aukema et al 2004;Boone et al 2009;Dahlsten et al 2003;Lanier et al 1972;Raffa and Dahlsten 1995;Senger and Roitberg 1992). However, neither auditory nor vibration perception has not been demonstrated for any of the invertebrate predators listed above.…”
Section: Anti-predator Function Of Disturbance Signalsmentioning
confidence: 99%